New generation ceramic membranes have the potential of removing endotoxins from dialysis water and dialysate - Czermak, Peter; Ebrahimi, Mehrdad; Catapano, Gerardo (My University, 2010)
Poor water properties, use of concentrated bicarbonate, and biofilm growth in pipes and storage tanks often cause dialysis water and dialysate contamination with bacteria and endotoxins. High-flux dialysis with bicarbonate may favour endotoxin transfer from the dialysate into the blood exposing patients to serious short and long term side effects. Ultrafiltration across hydrophobic synthetic membranes effectively remove endotoxins from dialysis water by combined filtration and adsorption. However, repeated sterilization worsens the membrane separation properties, and limits their use. Ceramic membranes are generally more resistant to harsh operating conditions than polymeric membranes, and may represent an alternative for endotoxin removal. Previously, we proved that the ceramic membranes commercially available at that time were not retentive enough to ensure production of endotoxin-free dialysis water. In this paper, we investigated the endotoxin removal capacity of new generation commercial ceramic membranes with nominal molecular weight cut-off down to 1,000. In dead-end filtration, all investigated membranes produced water meeting, or close to, the European standards when challenged with low endotoxin concentrations, but only one membrane type succeeded at high endotoxin concentrations. In cross-flow filtration, none produced water meeting the European standard. Moreover, sterilization and rinsing procedures altered the separation properties of two out of three membrane types.
Keywords: Ceramic; Dialysis; Membrane; Sterilization; Water